1997
DOI: 10.1074/jbc.272.16.10372
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Main Saccharide Chain in the Acrosome Reaction-inducing Substance of the Starfish, Asterias amurensis

Abstract: The structure of the main saccharide chain of the acrosome reaction-inducing substance in the egg jelly coat of the starfish, Asterias amurensis, is composed of the following pentasaccharide repeating units (Structure I). A polymer consisting of 10 -11 repeating units has been observed to induce the acrosome reaction in starfish sperm at high calcium concentrations. STRUCTURE IThe identities and linkage positions of constituent sugars were established using sugar, methylation, and sulfate analyses together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…We have recently found that sugar chain fragments liberated from ARIS or P-ARIS by ultra-sonication retains the biological activity of ARIS to an appreciable extent. The fragments are composed of 10 repeats or so of the following pentasaccharide unit and collectively named Fragment 1 (Koyota et al ., 1997):…”
Section: Introductionmentioning
confidence: 99%
“…We have recently found that sugar chain fragments liberated from ARIS or P-ARIS by ultra-sonication retains the biological activity of ARIS to an appreciable extent. The fragments are composed of 10 repeats or so of the following pentasaccharide unit and collectively named Fragment 1 (Koyota et al ., 1997):…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides sulfation per se, the proper spacing of sulfate groups seems essential for biological activity. A similar situation is suggested for ARIS (Koyota et al 1997). Also, as has been pointed out previously (Dhume & Lennarz 1995), sulfate groups might contribute to the unique properties of glycans and could probably amplify their recognition specificity.…”
Section: Discussionmentioning
confidence: 69%
“…While Xyl is sometimes found at terminal positions (both reducing and non-reducing) of glycans from animal glycoproteins, the presence of inner Xyl residues, deduced here from methylation analysis data, is rather unusual. Recently described acrosome reaction-inducing substance (ARIS) of the starfish Asterias amurensis is another example of glycan involved in fertilization and containing inner Xyl residues (Koyota et al 1997). Also, there have been a few reports of the occurrence of Ara or Rha in animal glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…In starfish, the giant pentasaccharide repeat polymer of EJ contains two sulfate groups per repeat. Solvolysis of the polymer shows that the loss of one sulfate per repeat greatly decreases its ability to induce the AR of starfish sperm (33).…”
Section: Discussionmentioning
confidence: 99%